“Are you a real Christian?”: Stereotypes, distrust and distinction strategies between “new” and “old” Protestants in Catalonia “És um verdadeiro cristão?”: Estereótipos, desconfiança e estratégias de diferenciação entre “novos” e “velhos” protestantes na Catalunha - Maria M. Griera (Etnográfica: Revista do Centro em Rede de Investigação em Antropologia, 2008)
The arrival of a high number of followers of the Protestant faith due to the increase in immigration flows has shaped the configuration, expectations for future growth and the public role of the Protestant community in Catalonia. However, the adaptation process between “new” and “old” Protestants has not been free of controversies. In this article, I deal with the analysis of the conflictive relationship between African Pentecostal Churches and the Catalan Protestant establishment. In order to do so, I explore the main transformations of the Catalan Protestant field (the phenomenon of reverse mission and above all the creation of ethnic churches) in recent times. The article is based on the fieldwork carried out among Protestant Churches in Catalonia between the years 2002 and 2006 and on ethnographic fieldwork carried out in an African church in Barcelona in 2004. A chegada (através do incremento de fluxos migratórios) de um número significativo de crentes à Catalunha alterou significativamente a configuração, expectativas de crescimento e lugar público da comunidade protestante daquela região. No entanto, o processo de adaptação entre “novos” e “velhos” protestantes não foi isento de controvérsia. Neste artigo, analiso a relação de conflito que se desenvolveu entre igrejas pentecostais africanas e o establishment protestante catalão. Para o fazer, exploro as principais transformações ocorridas no campo religioso protestante da Catalunha (o fenómeno de “missão reversa” e, sobretudo, a criação de “igrejas étnicas”) nos últimos tempos. Este artigo baseia-se em trabalho de campo etnográfico desenvolvido entre igrejas protestantes catalãs entre 2002 e 2006, e em particular numa igreja africana em Barcelona em 2004.